An Implement Scheme for Secure STB - Bingsong Hu; Xiaosang Huang (Dianxin kexue)
Android set-top box（STB）is well developed of its open and cross platform and the rich application.But security is one of the key issues of open systems.A software security scheme based on CPU for Android STB was proposed.By using OTP data and secure booting，the secure chain was set up to ensure safety of the software system，and the CPU based terminal authentication extends the secure domain to the CPE，provided the stability of the services.